Predicting Carbon Residual in Biomass Wastes Using Soft Computing Techniques - Preety Verma; J. Godwin Ponsam; Rajeev Shrivastava; Ajay Kushwaha; Neelabh Sao; AL Chockalingam; Leena Bojaraj; null JaikumarR; S. Chandragandhi; Assefa Alene (Adsorption Science & Technology)
In recent decades, the development of complex materials developed a class of biomass waste-derived porous carbons (BWDPCs), which are used for carbon capture and sustainable waste management. It is difficult in understanding the adsorption mechanism of CO2 in the air as it has a wide range of properties associated with its diverse textures, functional group existence, pressure, and temperature of varying range. These properties influence diversely the adsorption mechanism of CO2 and pose serious challenges in the process. To resolve this multiobjective formulation, we use a machine learning classifier that maps systematically the CO2 adsorption as a function of compositional and textural properties and adsorption parameters. The machine learning classifier helps in the classification of various porous carbon materials during the time of training and testing. The results of the simulation show that the proposed method is more efficient in classifying the porous nature of the CO2 adsorption materials than other methods.